2022
DOI: 10.4018/978-1-7998-9598-5.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Application of Inquiry-Based Science Education, Anticipatory Learning Strategy, and Project-Based Learning Strategies in the Context of Environmental Problems of the Contemporary World

Abstract: The global challenges of melting ice caps, rising global ocean levels, increased methane release from permafrost, and restrictions on access to water resources are primarily associated with climate change. Geographical education is of particular importance in this regard. At all levels of education, it should therefore provide knowledge about the changes taking place, shape practical skills, and foster the acquisition of appropriate attitudes in caring for the state of individual components of the geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Packing it with a game is one successful method of distribution. instructional games are games that may be customized for instructional purposes (Piotrowska et al, 2022;Rafique et al, 2020;Rohmah & Bukhori, 2020). Currently, educational games are in high demand as a means of conveying diverse learning materials by including challenges, incentives, and punishments into game design.…”
Section: Discussionmentioning
confidence: 99%
“…Packing it with a game is one successful method of distribution. instructional games are games that may be customized for instructional purposes (Piotrowska et al, 2022;Rafique et al, 2020;Rohmah & Bukhori, 2020). Currently, educational games are in high demand as a means of conveying diverse learning materials by including challenges, incentives, and punishments into game design.…”
Section: Discussionmentioning
confidence: 99%
“…All the major concepts were discussed, and then time was allowed for questions; results showed that, the students who attended the second type of review strategy out performed those in the former. Previous study noted that, students who attended one or more review classes earned higher grades than those that did not (Piotrowska et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…Regarding the Teaching Methodology, it is nothing more than the different processesthat the teacher carries out to achieve student learning, where the technique reflects the resources necessary for teaching (Piotrowska et al, 2022;Aza & Lica, 2019;Sabogal, 2015).…”
Section: Introductionmentioning
confidence: 99%